EFEKTIVITAS PENGGUNAAN JIGSAW DALAM MENINGKATKAN MOTIVASI BELAJAR PPKn KELAS X SMA ISLAM BAWARI PONTIANAK - Rahayu, Novia Sri; Utomo, Bambang Budi; Atmaja, Thomy Sastra (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe lack of motivations in learning that results in passive students in class activity have been a concern in this study. This study aims to find out the effectiveness of cooperative learning model using a jigsaw to improve students’ motivation in learning Civic Education. This is an experimental study on the tenth-grade students of SMA Islam Bawari Pontianak in the form of a quasi-experimental using non-equivalent control group design. Thirty-seven students from class X IIS 1 engaged in the control group, and Thirty-four from class X IIS 4 took part in the experimental group. The research instruments used were observation sheets, interviews, and documentation. The averages of learning motivation on the control group in meeting 1 and 2 are respectively 66,66% (high category) and 67,12% (high category), and in the experimental groups, the averages in meeting 1 and 2 are 78,12% (high category) and 80,94 (very high category). Based on the calculation, the effect size attained is 0,50, medium category. It shows that the applied learning model improves students’ motivation better than using a lecture method. Therefore, cooperative learning model using jigsaw can improve the class X IIS 4 students’ motivation in learning Civic Education at SMA Islam Bawari Pontianak. Keywords: Cooperative Learning Model, Effectiveness, Jigsaw, Learning Motivation Civic Education